2015
DOI: 10.9775/kvfd.2015.14391
|View full text |Cite
|
Sign up to set email alerts
|

Helikobakter Enfeksiyonlu Köpeklerde Demir Yetmezliği Anemisinin Belirlenmesi

Abstract: Many studies demonstrated that Helicobacter infections in humans affects iron metabolism and decreases ferritin level resulting with iron deficiency anemia. The aim of this study is the investigation of a correlation between Helicobacter infection and iron deficiency anemia in dogs. The material of the study consisted of 42 Helicobacter (+) (determined with polymerase chain reaction-PCR-following upper gastrointestinal system endoscopy) dogs (Group I) (n=42) referred with vomiting after feeding, anorexia and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In studies related to Helicobacter spp. in dogs, some haematological changes have been reported [16,17,18,19,20,21,22]. It has been reported that lymphocytosis due to lymphofollicular hyperpyloplasia occurs in dogs with Helicobacter infection [16].…”
Section: Correlation Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies related to Helicobacter spp. in dogs, some haematological changes have been reported [16,17,18,19,20,21,22]. It has been reported that lymphocytosis due to lymphofollicular hyperpyloplasia occurs in dogs with Helicobacter infection [16].…”
Section: Correlation Findingsmentioning
confidence: 99%
“…It has been reported that lymphocytosis due to lymphofollicular hyperpyloplasia occurs in dogs with Helicobacter infection [16]. Since Helicobacter agents can cause lymphoplastic, eosinophilic or chronic gastritis, neutrophilic leukocytosis is encountered in the blood in such cases [17]. Red blood cell (RBC) synthesis is regulated by many factors, such as erythropoietin, iron, vitamin B12, folic acid, and vitamin C. Decreases in erythropoietin, iron, vitamin B12, folic acid levels and, therefore, a decrease in RBC, can be observed in Helicobacter infections [9].…”
Section: Correlation Findingsmentioning
confidence: 99%